Implementasi Kebijakan Bogor Kerja Dalam Pelayanan Ketenagakerjaan Di Kota Bogor - Khan, Sahib; Tjenreng, M.B. Zubakhrum (Jurnal Inovasi Global, 2025)
The Bogor Kerja Program is an initiative of the Bogor City Government to improve employment services by utilizing information technology, in response to the open unemployment rate reaching 9.39% in 2023. The main objective of this program is to expand access to employment opportunities and make it easier for job seekers to obtain job vacancy information. This study examines the implementation of the Bogor Kerja policy through field studies, analysis of regional policy documents, and a review of relevant literature. A descriptive-qualitative approach was used with data collection techniques through observation, limited interviews with stakeholders, and document review. Research results show that this program has successfully created several new service mechanisms, such as an integrated job matching portal, online issuance of Yellow Cards (AK-1), e-ticketing innovations, and collaboration with the private sector in the form of hybrid job fairs. This program effectively helps the public access job vacancy information, reduces unemployment, and expands employment opportunities. However, challenges remain, such as a lack of program outreach, limited digital literacy among job seekers, and low company involvement. This study recommends increased outreach, training on digital platform use, cross-sector data integration, incentives for participating companies, and strengthening supporting regulations. With these steps, it is hoped that the Bogor Kerja program can develop into a more effective and inclusive public employment service innovation in Bogor City.